PROFESSIONAL TRAINING OF FUTURE TEACHERS OF GEOGRAPHY TO EXTRA-CURRICULAR WORK WITH STUDENTS - Dudka, Inna H. (Educological discourse, 2014)
Educational reform in Ukraine defines a fundamentally new quality of training and education of the young generation, capable of self-education, meaning ful identification of future life path, self-realization. The educational process in the school not only provides students for learning at a highlevel, but also promotes the development of cognitive interests, strength eningand improving the knowledge and skills acquired at the lessons. In addition within the frames of the training course the basics of physical and psychological health, hardening in tourist and regional workin conjunction of regional work and tourism as well as in the orientation contests, are formed. In this regard, special attention is paid to training of future teachers of geography, who can skill fully combine various forms and methods of work, to organize extra-curricular work of the students.